RELATIONSHIP OF WORKING SALARY, TEACHER RECOGNITION AND TEACHER COMMITMENT IN PRIVATE PRIMARY SCHOOL IN MUKUNGWE SUB-COUNTY, MASAKA DISTRICT. A CROSS-SECTIONAL STUDY. - Nansubuga, Cate Nabaggala; Sendagi, Muhammad (Student’s Journal of Health Research Africa, 2024)
Background: Private education in Uganda had a limited presence during the pre-independence era. Missionary schools played a significant role in providing education to the general population. The study aims to assess the relationship between working salary, teacher recognition, and teacher commitment in private primary schools in Mukungwe Sub-county, Masaka district. Methodology: A descriptive, cross-sectional, and correlational survey design. A qualitative approach was employed in examining the non-numerical findings of the study such as gender and attitudes of the respondents on the study variables were coded and summarized to produce descriptive findings. The quantitative approach was used to analyze and interpret numerical data for meaningful findings. Results: Among the respondents, 53% were male, while 47% were female. There was a strong positive correlation between working salary and teacher commitment (Pearson Correlation = 0.749, p = 0.001). This indicates that as working salary increases, teacher commitment also tends to increase. Similarly, there is a strong positive correlation between recognition and teacher commitment (Pearson Correlation = 0.683, p = 0.000). This suggests that when teachers feel recognized for their efforts, their commitment to their work also increases. Financial Constraints hindered teacher recognition eg “We rarely recognize teachers due to constraints on our income. We only appreciate their efforts on parade where they are given a hand clap” Conclusion: There was a strong positive relationship between working salary and teacher commitment indicating that as working salary increases, teacher commitment also tends to increase. A strong positive relationship between recognition and teacher commitment suggests that when teachers feel recognized for their efforts, their commitment to their work also increases. Recommendations. Private primary schools should ensure regular and timely payment of salaries to teachers, as it positively impacts their perceptions of working conditions and enhances commitment.